Global Staffing - Soetjipto, Budi W. (Forum Manajemen; Vol 10 No 62 (1996): Forum Manajemen Prasetiya Mulya | Zaman Revolusi Gelombang Ketiga dan lmplikasinya, 1996)
The polycentric approach has its own disadvantages as well. Perhaps the major disadvantage is that of bridging the gap between HCNs at national subsidiaries and PCNs at corporate headquarters.